Social enterprise: new way to do business in Malaysia / Roseamilda Mansor and Nurul Hayani Abd Rahman - Mansor, Roseamilda; Abd Rahman, Nurul Hayani (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Commercial enterprise was set up with the primary aim to get returns in terms of profit. However, for social enterprise, business solutions are used to solve social issues. Chandra et al. (2021) found that millennials are increasingly interested in social entrepreneurship as a career option. It is an approach by start-up companies and entrepreneurs to develop, fund, and implement solutions to social, cultural, or environmental issues. This concept may be applied to a wide range of organizations, which vary in terms of size, aims, and beliefs. Social entrepreneur is a kind of business entities who concern and not about the profit but at the same time give good return to the society. A previous study by Germak and Robinson (2014) found that social entrepreneurs were motivated to engage in social entrepreneurship by a desire to benefit society, which is a key characteristic of public service motivation. In addition, another study found that entrepreneurial intention is highly predicted by entrepreneurial self-efficacy when a strong perception of fit with entrepreneurship is attained. In contrast, regardless of entrepreneurial self-efficacy, if one perceives a low level of fit or no fit, entrepreneurial ambition will be low (Hsu et al., 2019).